Smedegårde og Livø - Marseen, Oscar (Kuml, 1962)
Smedegaarde and Livø Pitware Settlements on the Limfjord. Two years after C. J. Becker’s publication in 1950 of the Pitted Ware Culture in Denmark 1), the settlement at Selbjerg on Øland on the northern shore of the Limfjord was found, with pottery, flint implements and animal and fish bones 2). In the following year (1953), the settlement at Smedegaarde, in the parish of Nørre Tranders, was discovered. Smedegaarde is situated 4 km. east of Aalborg and about 4 km. south of the present Limfjord, and lies 6.35 m. above sea-level. The settlement originally lay on the west bank of an arm of the fjord. The area involved covered approximately 20 m. N-S and up to 10 m. E-W. As it transpired that no undisturbed stratum bearing artifacts was present, all material was carefully sieved to provide as large a statistical material as possible. The strongly arenacoous soil precludes the preservation of bones, and neither Cardium nor Ostrea shells were found, in contrast to Selbjerg. No post-holes were found in the light-coloured sub-soil and any dwellings there may have been have left no visible traces. Only the presence of fire-shattered granite provides evidence of fires, which, however, cannot be dated, as ploughing has destroyed the stratigraphy. The numerous potsherds represent such a large number of pots -at least 50- that a fairly long occupation may be assumed. No flint occurs near the site and the material used must have been brought from a distance. This is also seen by the absence of raw nodules, only worked flint being found. The site must, then, have been chosen with exclusive regard to food supply. In the inventory p. 00, Becker’s classification 7) of tanged arrowheads, which is based on differences in the dressing of the tang, has been adopted. This classification with its subdivisions A0, A1, A2, A3, (the points are all of A type) seems, however, too precise and specific to be of value for the Smedegaarde material, where there is an almost equal number of each type, and where it seems to be arbitrary, from which side the tang has been retouched. The arrowheads must be regarded as contemporary, also in view of the homogeneity of the pottery. The above considerations do not apply to type A0 (blade arrowhead without tang), however, which can only be determined as a type in integral finds 8). There are 6 specimens of A0, all having in common that they are flat at the base. This has been achieved not by dressing but in the striking of the blade, and permitted the point to be hafted without a tang. Only specimens with the tang intact are otherwise enumerated. Broken tips are not included. Of other flint implements, special mention should be made of the many blade scrapers and oblong flake scrapers. The latter agree well with the inventory from other Pitted Ware sites with A-points -Aagaard I, Øster Tørslev Parish, Randers Country, a site with an admixture of Ertebølle artifacts, where the inventory included 56 A-points, 71 cylinder flaking cores and 243 flake scrapers, of which the majority were oblong 9). Two flake axes, a core axe and seven transverse arrowheads and fragments of Late Neolithic implements such as daggers and sickles, also figure in the list, but such pieces are often found on the ancient coastline. Transverse arrowheads are, judging by Swedish settlements, not alien to the Pitted Ware culture. (It should be remarked that six are made from chips and the seventh from a blade. The latter therefore belongs to the Ertebølle culture). The pottery matrix is usually coarse and with a strong admixture of quartz, but well fired. The colour is most often brownish, but grey-black also occurs. The vast majority of the sherds are unornamented owing to the large size of the pots, which have been decorated only on or near the rim. It is rather unusual that the pots are also decorated on the edge itself (fig. 3). Only 12 small base sherds were found; 3 of them may be of round-bottomed vessels, the remainder have a flat base. Some of the latter can, however, be from Late Neolithic vessels, of which a few side-sherds were found. An examination of pitted ware potsherds in Swedish museums, and comparison with published Swedish pottery, reveals that the Smedegaarde pottery and the west Swedish pitware pottery from Bohuslän are so much alike, that the same culture must be responsible for both. Livø. During 1961 and 1962, 190 sq. m. of this settlement, which extends roughly 16 m. north-south and 20 m. east-west, on the cliff at the south of the island, were examined. On the surface of the light, greyish loam lay a great deal of ploughed-up flint waste. The pitware artifacts were found throughout the undisturbed stratum, which is up to 20 cm. thick and lies directly on the sand subsoil, but it was not possible to discern any stratification. Conditions were not suitable for the preservation of bone. As the site, which is situated on a low stretch of sand, surrounded by clay subsoil, has been open since its occupation, apart from a later covering of soil and blown sand, the same reservations as to possible intrusions apply as to other open Stone Age sites. But as a whole, it is regarded as a Pitted Ware site. The potsherds are generally coarse, with a strong quartz admixture, but well fired, although thin sherds with a smooth surface and a finer quartz admixture also occur. The colour varies from yellow-brown to black-grey. The smaller inventory, p. 128, in contrast to both Smedegaarde and the Pitted Ware settlements in Sweden indicates a shorter period of habitation, and this is confirmed by another interesting piece of evidence. Several rocks, resting on the subsoil, were uncovered. Around them were quantities of flint swarf and hammer stones, blades, cylindrical flaking cores and unfinished or rejected cores. They are anvil stones, where at least the coarser preparation took place. They were usually pointed, like small bauta stones, with shattering on or near the top. Fig. 13 shows a still erect anvil stone, surrounded by hammer stones and some flint waste. Fig. 15 shows an overturned anvil closely surrounded by hammer stones and swarf. In both cases most of the waste and all artifacts have been removed to clear the anvils for photography. The growth of swarf around them was clearly indicated and demonstrates that the layer is Pitted Ware throughout and deposited quite rapidly. These flint workshops with anvils confirm Anders Kragh’s arguments on flint technique 11). It is apparent from the rejected or unfinished blocks that it is the locally available dark shore-flint that was employed. Several of them still have the retouched sharp platform, which is the prerequisite for striking a keeled blade-in other words a keeled blade that has not been struck. In KUML 195316) I suggested that keeled blades must be regarded as a waste product. But this view, which was already challenged by Bengt Salomonsson in 1960 17), is disproved by the Livø site. Besides the tanged points, there are also 20 burins and 8 scrapers made from keeled blades (fig. 7-10). The Livø burins are robust and many of them can be seen to have been used repeatedly after re-cutting. This is particularly mentioned because it suggests that burins have been a natural and traditional tool for the Pitted Ware people. That so few as 5 were found at Smedegaarde is explained by the lack of opportunity to hunt seals or larger animals and the consequent reduced demand for burins, which are believed to be for working bone. The numerous dispersed pieces of amber found must be seen as evidence that one of the purposes of the settlement was the systematic collection of this material -a previously unknown side of the Pitted Ware peoples economy. The site must also have been chosen, not only for its fishing and seal-hunting but for its ready supply of flint, of which there are great quantities on the shore. From the flint inventory it appears that it is almost exclusively arrowheads and flake and blade implements that have been manufactured here and that it is the dark shore flint which has been employed. The axe fragments found are for the most part made of light, fine flint, which, at least at the present, is not found on Livø. Besides these, a "double edged" battleaxe of greenstone (fig. 11) was found in several pieces, in such circumstances that there seems to be no doubt as to its belonging to the Pitted Ware site. Such axes also occur at Swedish Pitted Ware sites 15). Flint implements and waste are largely unpatinated, but an experimental exposure to the elements demonstrated surprisingly that only one year is necessary to produce a blue-white patina. Traces of a horseshoe-shaped hut were found, but cannot be ascribed with certainty to the Pitted Ware habitation, (fig. 16). The results from the three Pitted Ware settlements, Selbjerg, Smedegaarde and Livø, which have all been published, supplement and confirm Becker’s documentation in 1950 1) of the role of the Pitted Ware people in Denmark. Oscar Marseen